1997
DOI: 10.1105/tpc.9.12.2143
|View full text |Cite
|
Sign up to set email alerts
|

The dominant developmental mutants of tomato, Mouse-ear and Curl, are associated with distinct modes of abnormal transcriptional regulation of a Knotted gene.

Abstract: The Curl (Cu) and Mouse-ear (Me) mutations of tomato cause two seemingly unrelated developmental syndromes with a wide range of pleiotropic phenotypes. Yet, the distinct morphogenic alterations in shoots, leaves, and inflorescences conferred by the two mutations appear to be caused by unchecked meristematic activity that characterizes dominant mutations in Knottedl (Knf)-like genes of monocot plants. We have been unable to separate the two closely linked Cu and Me mutations, and they may lie in the same gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 37 publications
5
74
1
1
Order By: Relevance
“…To determine the expression pattern of LeT6 in various tissues, we performed in situ RNA hybridization in shoot apices, mature leaves, and carpels derived from wild-type and clau:shl mutant plants. Consistent with previous reports (Chen et al, 1997;Parnis et al, 1997;Janssen et al, 1998aJanssen et al, , 1998b, LeT6 was found to be expressed in wild-type meristems, leaf primordia (not shown), as well as vascular tissues (Fig. 5B), but not in mature wild-type leaflets (Fig.…”
Section: Misexpression Of the Let6/tkn2 Gene In Mature Leaves And In supporting
confidence: 82%
See 2 more Smart Citations
“…To determine the expression pattern of LeT6 in various tissues, we performed in situ RNA hybridization in shoot apices, mature leaves, and carpels derived from wild-type and clau:shl mutant plants. Consistent with previous reports (Chen et al, 1997;Parnis et al, 1997;Janssen et al, 1998aJanssen et al, , 1998b, LeT6 was found to be expressed in wild-type meristems, leaf primordia (not shown), as well as vascular tissues (Fig. 5B), but not in mature wild-type leaflets (Fig.…”
Section: Misexpression Of the Let6/tkn2 Gene In Mature Leaves And In supporting
confidence: 82%
“…This is different from the adherent1 (ad1) mutant of maize in which tissue identity is preserved at the attached region (Sinha and Lynch, 1998). The control over organ fusion in the clau mutant cannot be solely attributed to LeT6, because tomato plants misexpressing this gene do not exhibit fusion of organs (Chen et al, 1997;Janssen et al, 1998a;Parnis et al, 1997). Taken together, the phenotypic alterations exerted by the clau mutation suggest that CLAUSA is involved not only in controlling the expression pattern of LeT6, but also in the control of other developmental genes in tomato plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dominant Mouse ear (Me) and Curl (Cu) mutations cause aberrant transcription of the tomato Tkn2 gene, yet Me leaves vary between highly ramified vegetative leaves and bladeless reproductive leaves, while the growth of Cu leaves is severely arrested (Parnis et al, 1997). Variation in the expression domain of ARP repressors during development may influence these phenotypes; however, ARP expression has been reported to be both absent and present in the SAM of tomato so this issue requires further investigation (Kim et al, 2003;Pien et al, 2001).…”
Section: A Matter Of Context: Competence To Respond To Knox Expressionmentioning
confidence: 99%
“…The encoded homeodomain transcription factors delay maturation and thereby facilitate the formation of leaflets (8). Overexpression of KNOXI genes during tomato leaf development leads to a strong increase in leaf complexity (5,28,29,36). We tested the interrelation between LeT6/TKn2 gene activity and Tf function by combining KNOXI gain of function mutants showing an increased leaf complexity with the tf mutation.…”
Section: Discussionmentioning
confidence: 99%